Corticosteroids for community-acquired pneumonia in non-ICU patients presenting to the emergency department: a systematic review and meta-analysis - Hanin A. Alhodathi; Hend M. Hussein; Shamael M. Alali; Zainab A. Hasan; Abdullah M. Al. Hussain; Almohanad A. Sait; Hassan A. Alali; Janah M. Almahdi; Jawad A. Alomaishi; Elaf S. Alzahrani; Abdullah Y. A. Alharbi; Alaa A. Alsaegh (International Journal Of Community Medicine And Public Health, 2026)
Community-acquired pneumonia (CAP) is among the most common infectious indications for emergency department attendance and hospitalization and carries a heavy mortality burden despite advances in antimicrobial therapy. Because a dysregulated host inflammatory response independently drives clinical deterioration, corticosteroids have been proposed as adjunctive treatment, but their benefit in non-ICU patients presenting to the emergency department remains unclear. A systematic search of PubMed, Web of Science, and EMBASE was conducted to identify randomized controlled trials evaluating systemic corticosteroids versus placebo or standard care in adults with CAP managed outside the ICU. The primary outcome was all-cause mortality; secondary outcomes included time to clinical stability, length of hospital stays, ICU admission, and adverse events. Twelve RCTs were included. Pooled analysis showed no significant difference in mortality between the corticosteroid and control groups (RR=0.98, 95% CI: 0.87–1.10, p=0.71; I²=0%). Neither time to clinical stability nor length of hospital stay differed significantly between groups, though both outcomes showed substantial heterogeneity. Corticosteroid use was associated with a significantly higher risk of hospital readmission (RR=1.35, 95% CI: 1.11–1.64, p